Cave Actinobacteria as Producers of Bioactive Metabolites - Rangseekaew, Pharada; Pathom-aree, Wasu (Frontiers in Microbiology, 2019)
Recently, there is an urgent need for new drugs due to the emergence of drug resistant pathogenic microorganisms and new infectious diseases. Members of phylum Actinobacteria are promising source of bioactive compounds notably antibiotics. The search for such new compounds is shifted to extreme or underexplored environments to increase the possibility of discovery. Cave ecosystems have attracted interest of research community because of their unique characteristics and the microbiome residing inside including actinobacteria. At the time of writing, 42 species in 28 genera of actinobacteira are reported from cave habitats. Novel and promising bioactive compounds have been isolated and characterized. This present mini-review focuses on diversity of actinobacteria in cave environments and bioactive metabolites produced by these cave associated actinobacteria from 1999-2018.